Optimalisasi Kromatogram Minyak Atsiri Batang Sereh Wangi bermetode GCMS Berpotensi sebagai Agen Antioksidan Alami dan Antibakteri - Ni Made sukma Sanjiwani; Agung Ari Chandra Wibawa; I Wayan Surya Rahadi; Dewa Ayu Sri Handani; I Gusti Ayu Agung Dwita Setya Cahyani; I Made Wisnu Yoga Pramana (Chemistry Department, 2026)
Essential oil from citronella (Cymbopogon nardus L), namely from the stem, is the main essential oil and antioxidant. The purpose of this study is firstly to determine what secondary metabolite compounds have potential as antioxidants and antibacterials using GCMS method. Second, to determine the optimum injection time (shown from the best chromatogram) in the identification of citronella stem essential oil in vitro using GCMS method. Third, to determine the antioxidant activity of citronella essential oil in vitro using DPPH and ABTS methods. Fourth, to determine the antibacterial activity of citronella essential oil in vitro using Staphylococcus aureus bacteria. Essential oil was processed by steam distillation. Optimisation of the chromatogram of fragrant lemongrass stem essential oil using GCMS method was carried out through 6 variations in the length of injection time, namely: 21, 39, 40, 42, 46 and 50 minutes. Antioxidant activity was tested using DPPH and ABTS methods. Antibacterial activity test was conducted in vitro using Staphylococcus aureus bacteria. The compounds contained in the chromatogram results of 6 variations of injection time, compounds that have the potential as antioxidants are Limonen, isopulegol, citral, Citronellal, Citronellyl isobutyrate, Geranyl acetate, Caryophyllene, Germacrene D and Naphthalene. These compounds can counteract free radicals. Compounds that have antibacterial potential are Citronellol, Geraniol, Citronellyl isobutyrate, Geranyl acetate, Caryophyllene, Germacrene D and Naphthalene. These compounds can inhibit bacterial growth. Based on 6 variations of injection time, the optimum injection time is obtained at 46 minutes because at that time the chromatogram of citronella stem essential oil shows the best peak because the peak is not too close together so it is not destroyed. Citronella oil has a very strong antioxidant activity category both by DPPH and ABTS methods. Fragrant lemongrass stem oil has a weak antibacterial activity category against Staphylococcus aureus bacteria.